2017
DOI: 10.3892/etm.2017.4882
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of miR-181b in heart disease due to pregnancy-induced hypertension syndrome

Abstract: The present study aimed to investigate the molecular mechanisms of microRNA (miR)-181b in heart disease due to hypertensive disorders complicating pregnancy (HDCP) through regulating the expression of metallopeptidase inhibitor 3 (TIMP3). miR-181b expression was detected by reverse transcription-quantitative polymerase chain reaction in peripheral blood samples from patients with HDCP. These samples were analyzed for clinical pathological characteristics. The primary cardiomyocytes of rats were cultured in hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Through binding to, and inhibiting Timp3 expression, miR-21 enhances survival, migration and capillary formation ability of human umbilical vein endothelial cell lines (HUVECs) (Hu et al, 2016). miR-181b targets Timp3 and reduces apoptosis of cardiomyocytes (Gao et al, 2017), but enhances gelatinases/MMP activity in human aortic valve endothelial cells which may contribute to calcific aortic valve disease (Heath et al, 2018). MiR-181b is increased in human atherosclerotic plaques and abdominal aortic aneurysms (AAA), and inhibition of miR-181b suppressed the development and progression of atherosclerosis and aneurysms through increasing expression of TIMP3, elastin, and collagen (Di Gregoli et al, 2017).…”
Section: Micrornas Bind To and Downregulate Timp3mentioning
confidence: 99%
See 1 more Smart Citation
“…Through binding to, and inhibiting Timp3 expression, miR-21 enhances survival, migration and capillary formation ability of human umbilical vein endothelial cell lines (HUVECs) (Hu et al, 2016). miR-181b targets Timp3 and reduces apoptosis of cardiomyocytes (Gao et al, 2017), but enhances gelatinases/MMP activity in human aortic valve endothelial cells which may contribute to calcific aortic valve disease (Heath et al, 2018). MiR-181b is increased in human atherosclerotic plaques and abdominal aortic aneurysms (AAA), and inhibition of miR-181b suppressed the development and progression of atherosclerosis and aneurysms through increasing expression of TIMP3, elastin, and collagen (Di Gregoli et al, 2017).…”
Section: Micrornas Bind To and Downregulate Timp3mentioning
confidence: 99%
“…Since in vitro experiments lack the multicellular interactions that exist in vivo, the results from in vitro studies may differ from those in vivo. An in vitro study showed that silencing TIMP3 reduces apoptosis of cardiomyocytes isolated from 5 to 6 week-old female rats (Gao et al, 2017). However, deficiency or inhibition of TIMP3 enhances neonatal mouse cardiomyocyte proliferation in vitro and in vivo, which can be inhibited by treatment with recombinant TIMP3, through a mechanism involving inhibition of MMP activity and EGFR/JNK/SP-1 signaling pathway (Hammoud et al, 2009;Shi et al, 2017).…”
Section: Timp3 In Cardiovascular Pathologies Timp3 In Myocardial Diseasementioning
confidence: 99%
“…miR-181a has been confirmed to be cardioprotective under myocardial infarction stress by reducing aldosterone-mineralocorticoid receptor-mediated cardiac remodeling . Moreover, miR-181b inhibits the apoptosis of cardiomyocytes and protects cardiomyocytes in heart disease due to pregnancy-induced hypertension syndrome . miR-181 can directly target early growth response 1 (EGR1), which is an immediate master regulator gene conferring an integral role in the pathophysiology of various cardiovascular diseases …”
Section: Introductionmentioning
confidence: 99%
“…miRNA is a noncoding RNA, which can regulate downstream signaling pathway and thereby regulate the relevant biological activities 25–29. In the present study, the blood pressure in the miR‐106a‐mimic group was lower than in the model group, revealing that miR‐106a overexpression can reduce the blood pressure of GH mice.…”
Section: Discussionmentioning
confidence: 45%